Individual effects of GSTM1 and GSTT1 polymorphisms on cervical or ovarian cancer risk: An updated meta-analysis - Ye, Jing; Mu, Yi-Yang; Wang, Jiong; He, Xiao-Feng (Frontiers in Genetics, 2023)
Background: Studies have shown that glutathione S-transferase M1 (GSTM1) and glutathione S-transferase T1 (GSTT1) null genotype may increase the risk of cervical cancer (CC) or ovarian cancer (OC), however, the results of published original studies and meta-analyses are inconsistent. Objectives: To investigate the association between GSTM1 present/null and GSTT1 present/null polymorphisms,with the risk of CC or OC. Methods: The odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the association between GSTM1 present/null and GSTT1 present/null polymorphisms and the risk of CC or OC. To assess the confidence of statistically significant associations, we applied false positive reporting probability (FPRP) and bayesian false discovery probability (BFDP) tests. Results: Overall analysis showed that GSTM1 null was associated with an increased risk of CC, and subgroup analysis showed a significant increase in CC risk in Indian and Chinese populations; GSTT1 was not found null genotype are significantly associated with CC. Overall analysis showed that GSTM1 and GSTT1 null were not associated with the risk of OC, subgroup analysis showed that GSTM1 null was associated with an increased risk of OC in East Asia, and GSTT1 null was associated with an increased risk of OC in South America. However, when we used FPRP and BFDP to verify the confidence of a significant association, all positive results showed "low confidence" (FPRP > 0.2, BFDP > 0.8). Conclusion: The results of this study suggest that GSTM1 null may increase the risk of CC, GSTM1 null may increase the risk of OC in East Asia, and GSTT1 null may increase the risk of OC in South America, But the related positive results may increase the risk of OC in East Asia. are results of missing confidence, not true associations, so these positive results should be interpreted and applied with caution.